2009
DOI: 10.2754/avb200978020259
|View full text |Cite
|
Sign up to set email alerts
|

Titres of Specific Antibodies against Toxoplasma gondii in Goats and their Kids

Abstract: The aim of our study was to perform repeated determination of specific antibody levels in mothers and their kids in order to assess indirectly the possibility of vertical transmission of toxoplasmosis in goats. Twenty-eight goats with their kids were included in the study. The following variables were assessed: number of born kids in relation to antibody titres of goats; levels of specific antibodies in the blood of goats and kids; and concentrations of immunoglobulins (Ig), total protein (TP) and total globul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
1
5
0
1
Order By: Relevance
“…In Europe, Toxoplasma gondii antibodies were found in the range of 5-91% in goats in Austria, Bulgaria, Croatia, Germany, Greece, France, Italy, Poland, Netherlands, Norway, Slovakia, Spain and Turkey (Dubey 2010). In the Czech Republic, a seroprevalence of 21% to 82% has been found in goats in previous studies (Hejlicek and Literak 1994;Slosarkova et al 1999;Misurova et al 2009). …”
mentioning
confidence: 75%
“…In Europe, Toxoplasma gondii antibodies were found in the range of 5-91% in goats in Austria, Bulgaria, Croatia, Germany, Greece, France, Italy, Poland, Netherlands, Norway, Slovakia, Spain and Turkey (Dubey 2010). In the Czech Republic, a seroprevalence of 21% to 82% has been found in goats in previous studies (Hejlicek and Literak 1994;Slosarkova et al 1999;Misurova et al 2009). …”
mentioning
confidence: 75%
“…gondii effects on foetal development which changed with female age. The protozoan appears not to directly affect the probability of being pregnant, unlike what was supposed in goats [ 53 ], but could indirectly affect red deer fertility impairing foetal development. In particular, this finding could be the consequence of an infection acquired before the breeding season which influenced females' fertility by delaying mating or pregnancy or decreasing the foetal development.…”
Section: Discussionmentioning
confidence: 99%
“…Earliest studies performed in European countries found that antibodies to T. gondii were detected even in 79% of tested goats and 24% of tested sheep (Misurova et al, 2009;Špilovská et al, 2009). They indicated that goats are associated with higher T. gondii seroprevalence than sheep.…”
Section: Discussionmentioning
confidence: 99%